Non-Native Species and Urbanization in the Context of Butterfly Communities - Rivest, Stephanie (Université d'Ottawa / University of Ottawa, 2023)
Biodiversity is being lost around the world and anthropogenic activities, like non-native species introductions and urbanization, are among the leading causes of decline. Broadening our understanding of human-driven impacts on biodiversity can lead to more effective solutions and contribute towards stemming biodiversity losses. In this thesis, I explored the impacts of non-native species introductions and urbanization on butterfly-plant communities. I evaluated potential factors influencing the range expansion of a newly introduced species (Chapter 1), examined the role of urbanization in structuring biological communities (Chapter 2), and identified important ecological interactions between native and non-native species (Chapter 3). In my first chapter, I found that the newly introduced European Common Blue butterfly (Polyommatus icarus) was more abundant in urban and disturbed habitat that was unmown and where their preferred larval host plant (Lotus corniculatus), a non-native species, was present. I also found that P. icarus was not a strong flier relative to other butterfly species, suggesting that adult dispersal may not be a driving factor in range expansion. Instead, this species could expand its range in the future by colonizing habitats in developed regions across Canada given the association I found between P. icarus and disturbed habitat. In my second chapter, I found that urbanization led to the biotic homogenization of butterfly communities around Montréal, QC, favouring a few, highly abundant, non-native species. Homogenization was detected at both the taxonomic and functional levels and was driven by increases in P. icarus abundance in the more urban sites. In my third chapter, I found that non-native plants were well integrated into native butterfly nectar diets in an at-risk oak savanna ecosystem on Vancouver Island, BC and that usage of non-native plants increased when they were more available during the season. I also found that native butterflies visited non-native plants more often than flower availability predicted on its own, suggesting that butterflies may even prefer non-native nectar. Findings from my thesis research broaden our understanding of the ways in which butterfly communities can be influenced by human activities like urbanization and the introduction of non-native species, informing conservation efforts and directing future research needs.
Keywords: butterfly; non-native species; urbanization; biotic homogenization; habitat suitability; phenology; species interactions; nectar; range expansion; land cover; anthropogenic disturbance; flower availability; community ecology; invasion ecology; resource selection; temporal ecology